Terminations of pregnancy in the European Union - Gissler, Mika; Jahn, Albrecht (BJOG, 2012)
Please cite this paper as: Gissler M, Fronteira I, Jahn A, Karro H, Moreau C, Oliveira da Silva M, Olsen J, Savona-Ventura C, Temmerman M, Hemminki E, the REPROSTAT group. Terminations of pregnancy in the European Union. BJOG 2011; DOI: 10.1111/j.1471-0528.2011.03189.x. Objective To study the current legislation and trends in terminations of pregnancy in the European Union (EU). Design Data were collected on legislation and statistics for terminations of pregnancy. Setting Population-based statistics from the EU member states. Population Women in reproductive age in the 27 EU member states. Methods Information on legislation was collected for all 27 EU member states. Statistical information until 2008 was compiled from international (n = 24) and national sources (n = 17). Statistical data were not available for Austria, Cyprus and Luxembourg. Main outcomes measures Terminations of pregnancy per 1000 women aged 15-49 years. Results Ireland, Malta and Poland have restrictive legislation. Luxembourg permits termination of pregnancy on physical and mental health indications; Cyprus, Finland, and the UK further include socio-economic indications. In all other EU member states termination of pregnancy can be performed in early pregnancy on a women’s request. In general, the rates of termination of pregnancy have declined in recent years. In total, 10.3 terminations were reported per 1000 women aged 15-49 years in the EU in 2008. The rate was 12.3/1000 for countries requiring a legal indication for termination, and 11.0/1000 for countries allowing termination on request. Northern Europe (10.9/1000) and Central and Eastern Europe (10.8/1000) had higher rates than Southern Europe (8.9/1000). Northern Europe, however, had substantially higher rates of termination of pregnancy among teenagers. Conclusion A more consistent and coherent reporting of terminations of pregnancy is needed in the EU. The large variation of termination rates between countries suggests that termination of pregnancy rates may be reduced in some countries without restricting women’s access to termination. Sexual education and provision of access to reliable and affordable contraception are essential to achieve low rates of termination of pregnancy.